Economic Policy of Shah Abbas the Great (Journal of the College of Basic Education, 2023)
Several Shahs succeeded in ruling the Safavid state, most notably Shah Abbas the Great. During his reign (1587-1629 AD) most of the goals of the Safavid state were embodied and reached the height of its strength and greatness as security was established and the state regained its prestige, and Shah Abbas the Great was able to eliminate all internal strife and rebellions. The army developed and equipped it with modern firearms, and during it it was able to recover all the lands that fell under the Ottoman and Uzbek occupation, and the Safavid state regained control over the Shiite holy places in Iraq, and Isfahan became its capital, and his reign was marked by the opening of Iran to Europe, where commercial and political treaties were concluded with other countries Europe with the aim of forming a front against the Ottoman Empire, the common enemy of both sides, and to find new markets for the sale of Iranian silk, and industries, arts and sciences flourished, and as a result of these great contributions, the personality of Shah Abbas the Great emerged as a symbol in the modern history of Iran.